A new species of Syzygium (Myrtaceae) from the Agasthyamalai Biosphere Reserve, Kerala, India - Sreekala, A. K.; Pillai, Divya S.; Akhil, R.; Surendran, Anjana; Ramasubbu, R. (Phytotaxa, 2019)
Syzygium ponmudianum, a new tree species from Ponmudi, Agasthyamalai Biosphere Reserve, Kerala, India is described. This species is closely allied to Syzygium benthamianum and S. myhendrae but differs from it by having a reddish brown coloured cylindrical stem, large sized leaves with 22-29 pairs of secondary veins, deltoid and persistent calyx lobes, pyriform hypanthium, variously statured filaments, deep purple berries with ovate seeds.